2019
DOI: 10.21931/rb/2019.04.01.4
|View full text |Cite
|
Sign up to set email alerts
|

AAV Purification by anion-exchange chromatography

Abstract: We describe a new optimized, scalable and reproducible method based on anion exchange chromatography to obtain high titers of rAAV vectors without empty capsids contamination. The method takes advantage of Q-sepharose matriz to development a scalable procedure. After the virus harvest from supernatant and lysate cells, virus crude was subjected to anion exchange chromatography with Q-sepharose column. Three different protocols were tested, and the elution peaks were evaluated through qPCR rAAV titration and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…One type of ion-exchange matrix is rarely used to obtain pure rAAV virions ready for preclinical and clinical studies. Most of the studies are based on the initial purification of rAAV by cation exchange chromatography (CX), [10,30,31] UC in a density gradient, [32][33][34][35] preliminary precipitation with PEG 8000, [36] followed by purification using a weak anionic exchange resin [8] or affinity chromatography (AC), [37,38] and then directly using anion exchange resins to effectively remove empty capsids (Table 1). Cation exchange resins are usually used as the first stage of viral purification from the cell lysate, since in a certain pH range these resins interact with cellular proteins and other contaminating components, but not with viral particles.…”
Section: Efficiency Of Raav Purification By the Ic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One type of ion-exchange matrix is rarely used to obtain pure rAAV virions ready for preclinical and clinical studies. Most of the studies are based on the initial purification of rAAV by cation exchange chromatography (CX), [10,30,31] UC in a density gradient, [32][33][34][35] preliminary precipitation with PEG 8000, [36] followed by purification using a weak anionic exchange resin [8] or affinity chromatography (AC), [37,38] and then directly using anion exchange resins to effectively remove empty capsids (Table 1). Cation exchange resins are usually used as the first stage of viral purification from the cell lysate, since in a certain pH range these resins interact with cellular proteins and other contaminating components, but not with viral particles.…”
Section: Efficiency Of Raav Purification By the Ic Methodsmentioning
confidence: 99%
“…[10] Similar results with a minimum content of empty capsids were obtained using AX on a Q Sepharose matrix with preliminary precipitation in 40% PEG 8000. [36] Kaludov et al [8] demonstrated the efficient removal of empty capsids of rAAV2, rAAV4, and rAAV5 using POROS PI and POROS HQ adsorbents. At the same time, the content of empty virions in the final viral preparation was less than 10%.…”
Section: Efficiency Of Raav Purification By the Ic Methodsmentioning
confidence: 99%
See 1 more Smart Citation